Retrenchment of euro area banks and international banking models - Isabel Argimón; Elena Fernández Ortiz; María Rodríguez-Moreno (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2020)
In this paper, we analyze the importance of international banking models, along the operational and the funding dimensions, for the decline in international positions of European banks since the crisis. Using BIS Consolidated Banking Statistics, we find that the multinational model (higher reliance on local activity) and the decentralized model (higher weight of local funding over local claims) is associated with lower retrenchment. We also find that more business synchronization between the home and the host economy is associated with higher declines in lending after the crisis and that the multinational and decentralized models mitigate such effect. On the other hand, lending to banks is not affected by the correlation of economic cycles between the home and the host country.
Keywords: F21; F23; G15; G21; 330; global banking; cross-border bank lending; financial crisis; retrenchment